Management of acute Arterial ischemia of the upper extremity experience in Tishreen university hospital in latakia (2022-2024) (Latakia University Journal -Medical Sciences Series, 2024)
Acute arterial ischemia of the upper extremity is an emergency condition during which the patient must be quickly transferred to the hospital and urgent consultation from a vascular surgeon is required, due to the seriousness of complications that may lead to death.It is considered one of the most common and dangerous emergency cases in vascular surgery, as this disease is a group of serious complications resulting from the sudden interruption of blood flow due to an obstruction in one of the arteries (the cause is often an embolism emanating from the heart).In the cause of emboli originating from the heart, 60% of them are usually directed to the brain, and of the remaining 40%, 80% of them go to the lower extremities, about 15% of them go to the upper extremities, and the rest goes to other destinations.Our study included 22 patients who visited the ambulance at Tishreen university hospital in Latakia between 01.01.2022 and 01.01.2024 with a complaint of acute arterial ischemia in the upper extremity. Our study dealt with the causes and management and was compared with international studies.In our study, we did not address acute traumatic obstruction resulting from accidents or errors medical or small thrombotic conditions in the fingers caused by peripheral vascular diseases.